Light-weight shape and topology optimization with hybrid deposition path planning for FDM parts - Liu, Jikai; Ma, Yongsheng; Qureshi, A. J.; Ahmad, Rafiq (International journal of advanced manufacturing technology, 2018)
FDM (fused deposition modeling) parts demonstrate anisotropic properties between the in-layer raster and transverse directions. However, structural optimization of FDM parts has rarely taken the deposition path and thus the anisotropic material properties into consideration. This work proposes a methodology that integrates optimal hybrid deposition paths with the shape and topology optimization and brings all aspects under a unified level set framework. A dedicated sensitivity analysis is performed on both the shape and path variables, which ensures the optimality of the derived design solutions. Effectiveness of the proposed method is demonstrated through a number of 2D and 3D numerical examples.